SINERGITAS DENSUS 88 ANTI TEROR DENGAN PERGURUAN TINGGI DALAM MENCEGAH RADIKALISASI BERDASARKAN UNDANG-UNDANG NO 5 TAHUN 2018 TENTANG TERORISME - Priyanto, Rahmat Cok (Kerta Dyatmika, 2018)
The phenomenon of instilling radical ideas in students at universities is a very dangerous form of crime, this has even happened in the province of Bali. From the explanation above, several problems can be formulated, including: What is the synergy of Densus 88 Anti-Terror with Universities in preventing radicalization? based on Law Number 5 of 2018 concerning Terrorism? and what prevention efforts have been carried out by Densus 88 Anti-Terror with Universities to prevent radicalization based on Law Number 5 of 2018 concerning Terrorism? The type of research used in this research is empirical juridical research. This type of empirical juridical research is research that examines and analyzes the operation of law in society (law in action). The main data used is data sourced from the field.. A form of synergy between Densus 88 Anti-Terror and Higher Education Institutions in preventing radicalization based on Law Number 5 of 2018 concerning Terrorism is holding webinars at Higher Education Institutions where this webinar activity is a preventive step to prevent radicalism in the tertiary environment, with a declaration which emphasizes national values, anti-radicalism/terrorism, and love of the country. As well as prevention efforts that have been carried out by Densus 88 Anti-Terror with Higher Education Institutions to prevent radicalization based on Law Number 5 of 2018 concerning Terrorism, namely by holding seminars, workshops and educational programs about radicalization and its prevention to increase awareness and understanding of students and academic staff as well as Building a Positive Narrative by Using social media and other platforms to build a positive narrative about the importance of this collaboration in preventing radicalization.